The use of phonophoresis in pain and functionality in individuals with knee osteoarthritis: A review of the scope (Research, Society and Development, 2021)
The objective of this scope review was to map and synthesize evidence regarding the use of phonophoresis for pain and functionality in knee osteoarthritis, as well as to seek which parameters/drugs are being used in this technique. The databases used to search for articles were: PubMed, Virtual Health Library, SciELO, PEDro, and gray literature sources, published in the period between April 2011 and March 2021. Studies carried out in individuals with osteoarthritis were considered, who were treated with phonophoresis for pain and functionality, in any clinical and geographic context. After the searches, 7 articles were included in this review, which show positive results of phonophoresis in the impacts of knee osteoarthritis. In conclusion, phonophoresis is effective in relieving pain and improving functionality in individuals with knee osteoarthritis.